Thamnīap sattrī phūnam kānplīanpl̄æng phalang sāngsan nai kānphatthanā prathēt (Sathāban Wičhai Botbāt Ying Chāi læ kānphatthanā, 1996)
Directory of women leading in development activities in Thailand.